Effectiveness of Home Visiting Programs To Prevent Maternal Depression: A Systematic Review of RCTs - Liem, Jean Andrina; Rustiadi, Natalie Debora Devino; Wijovi, Felix; Heriyanto, Rivaldo Steven; Setyoputra, Bryan; Sucahyo, Emanuela Clarisa Karina; Lake, Josephus Rivaldo; Aurielle, Celine; Handoko, Marshell Timotius; Cipta, Darien Alfa (Faculty of Medicine, Public Health, and Nursing, 2023)
During prenatal and post-partum period, 10-20% of women experience depression. The quality of life and functional capacity of these women were also significantly impacted by depression. This condition also has an adverse effect on fetal development and newborn. Furthermore, home visit have been used to reduce maternal depression. However, the evidence of this still low. Hence, this review aims to evaluate the effectiveness of home visiting in preventing maternal depression. Articles for this systematic review were collected from several databases (PubMed, Scopus, Google Scholar, and ScienceDirect) using terms related to maternal depression, prevention, and home visiting. The quality of included studies were assessed using the Newcastle-Ottawa Scale (NOS). This systematic review is comprised of 13 high quality randomized clinical trials with 4.804 participants. Eleven studies indicate that home visiting effectively reduce depressive symptoms and a study shows that mothers receiving home visiting are twice less likely to develop depressive symptoms. Home visiting are also beneficial for low-income women amidst the low rate of mental health services. Only two studies state that there is no evidence that home visiting effectively reduces depressive symptoms and increases caregiving quality. However, some studies state that the mother's cognitive, child growth, and maternal depression may improve with home visiting integrated with cognitive behavioral therapy, counseling, education such as lectures, or video. Home visiting are effective in preventing maternal depression. Further studies are needed to compare the effectiveness of the intervention plan in home visiting.